Pengaruh Penggunaan Media Kahoot terhadap Minat Belajar Siswa dalam Mata Pelajaran PAI di SMP Negeri 35 Padang - Fitri, Yuliana; Wardefi, Riza (TSAQOFAH, 2025)
The lack of student interest in Islamic Religious Education (PAI) at SMP Negeri 35 Padang highlights the need for innovative instructional media that can enhance student engagement. This study aims to analyze the effect of using Kahoot as a learning medium on the learning interest of eighth-grade students in PAI. A quantitative approach with a correlational method was employed. The sample consisted of 61 students from classes VIII-1, VIII-2, and VIII-5, selected using the Slovin formula. Research instruments included a learning interest questionnaire and students' academic scores. Data analysis was conducted using simple linear regression with SPSS version 30. The results show that the use of Kahoot has a positive and significant influence on students’ learning interest, with a relatively high level of effect. These findings support the theory that interactive learning media can enhance students' motivation and engagement in the learning process. The study concludes that Kahoot is an effective learning medium for increasing student interest in PAI. The implications include a theoretical contribution to the literature on digital media in education and practical recommendations for teachers to integrate Kahoot as an innovative and interactive learning tool. This research also opens opportunities for further studies on the effectiveness of other digital media in influencing students' affective and cognitive domains.